Comparative studies on the biochemical properties of the malic enzymes fromTrypanosoma cruzi andTrypanosoma brucei - Leroux, Alejandro Ezequiel (2011)
Comparative studies showed that, like Trypanosoma cruzi, Trypanosoma brucei exhibits functional cytosolic and mitochondrial malic enzymes (MEs), which are specifically linked to NADP. Kinetic studies provided evidence that T. cruzi and T.brucei MEs display similarly high affinities towards NADP1 and are also almost equally efficient in catalyzing the production of NADPH. Nevertheless, in contrast to the cytosolic ME from T. cruzi, which is highly activated by L-aspartate (over 10-fold), the T. brucei homologue is slightly more active (50%) in the presence of this amino acid. In T. brucei, both isozymes appear to be clearly more abundant in the insect stage, although they can be immunodetected in the bloodstream forms. By contrast, in T. cruzi the expression of the mitochondrial ME seems to be clearly upregulated in amastigotes, whereas the cytosolic isoform appears to be more abundant in the insect stages of the parasite. It might be hypothesized that in those environments where glucose is very low or absent, these pathogens depend on NADP-linked dehydrogenases such as the MEs for NADPH production, as in those conditions the pentose phosphate pathway cannot serve as a source of essential reducing power.